Consumption Smoothing and the Structure of Labor and Credit Markets - Giuseppe Bertola; Winfried Koeniger (Institute for the Study of Labor (IZA), 2004)
Smoother labor incomes alleviate credit constraints by reducing workers' desire to borrow, and prospects of upward income mobility have smaller beneficial effects for currently poor workers when borrowing constraints are binding. These simple theoretical insights are consistent with the empirically more pronounced tendency of poor would-borrowers to favor government redistribution in countries where consumer credit is relatively scarce. They may also explain observed institutional patterns across countries and markets: policies that reduce the dispersion and volatility of labor income appear to be more prevalent in countries where inefficient legal systems restrict borrowing opportunities. Our theoretical perspective and empirical results offer more general insights as to ways in which historically determined features and politico-economic interactions may jointly shape institutional aspects of different markets, and as to appropriate design of reform processes.
Keywords: E21; E61; E24; 330; labor market institutions; consumer credit; redistribution; borrowing constraints; Lohn; Gesamtwirtschaftlicher Konsum; Volatilität; Verschuldungsrestriktion; Arbeitsmarktflexibilisierung; Verbraucherkredit; Einkommensumverteilung; Schätzung; Theorie; OECD-Staaten